Faktor Faktor Yang Mempengaruhi Kinerja Karyawan Bank Muamalat Kota Malang : Kepuasan Kerja Sebagai Variabel Intervening - Muhammad Fariz Al'Fattah; Siswanto, Siswanto (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
This study was conducted to test and analyze the factors that can affect the performance of employees of Bank Muamalat Malang City through variables: working hours, compensation, job stress with job satisfaction as an intervening variable. The population used amounted to 45 people who came from employees of Bank Muamalat Malang City. The sampling technique uses a saturated sample method which is part of non probability sampling. The results of the study directly revealed that working hours affect employee performance, while compensation and job stress have no effect. In indirect research results through intervening variables, there is a partial mediation effect between work stress and employee performance, there is no mediation effect between compensation and employee performance and there is a full mediation effect between work stress and employee performance.